The effect of Double Taxation Treaties and Territorial Tax Systems on Foreign Direct Investment: Evidence for Spain - Ángela Castillo-Murciego; Julio López Laborda (Kiel Institute for the World Economy (IfW), 2018)
The present paper evaluates the effect of Double Taxation Treaties and the Territorial Tax System of countries on Spain's inward and outward FDI for the period 1993-2013. Estimations produce a positive and statistically significant effect of Treaties for both samples when using a simple binary variable for measuring the effect of the mere existence of the same. These outcomes keep for old and new Treaties and for the sub-sample of developed partner countries of Spain. However, regarding developing countries, the positive result exists only for the outbound sample. Also for the global samples and the sub-samples of developed countries, there is an additional positive effect on investments for countries applying the Territorial Tax System for taxing foreign income.
Keywords: F21; F23; F68; H25; H32; H87; 330; Foreign Direct Investment; Double Taxation Treaty; Territorial Tax System; Spain